Nested array receiver with time‐delayers for joint target range and angle estimation. Issue 8 (1st October 2016) - Wang, Wen‐Qin; Zhu, Chenglong
Abstract : Phased‐array provides range‐independent beampattern and consequently it cannot detect/suppress range‐dependent targets/interferences. Moreover, an M ‐element phased‐array can resolve at most M − 1 targets simultaneously. This study proposes a nested array receiver using diverse time‐delayers (DTDs) for jointly estimating the range and angle of targets. The essence is to construct a new array structure by systematically nesting two uniform linear arrays through DTDs instead of phase controlling in traditional nested array technique. Using the second‐order statistics of the received data, an M ‐element array can resolve O ( M 2 ) targets. Moreover, the nested DTD receiver design is exploited for minimum variance distortionless response beamforming and direction finding. The improvements offered by the proposed method, as compared with basic DTD receivers, are demonstrated by examining the output signal‐to‐interference‐plus‐noise ratio, the probability of detection and the Cramér–Rao lower bounds for estimating the range and angle of targets.